Seed of rice plant classification using coarse tree classifier - Kim Wallie Vergara Geollegue; Edwin Romeroso Arboleda; Andy Agustin Dizon (Institute of Advanced Engineering and Science, 2022)
The goal of this paper is to help the agriculture to have consistent observation in the status of seeds in rice plants and have a good quality postproduction by classifying the seeds automatically leading to reduction of low-quality rice plants while achieving higher demands in exportation as the quality increases. Additionally, manually observing the seeds of rice plants does not give an accurate evaluation as factors such as fatigue and emotion can affect the result. Using image processing and color feature extraction, it extracted the red, green, and blue (RGB) color feature lying in the pixel point of the seed in the healthy and unhealthy images of rice plants and classified by coarse tree classifier (CTC). The classifier achieved a 100% accuracy and training time of 0.32189 seconds, hence the fitted machine learning approach in the study.